A Novel Method of Synthesis of Nanostructured Aluminum Nitride Through Sol‐Gel Route by In Situ Generation of Nitrogen. Issue 2 (7th January 2013) - Ghosh Chaudhuri, M.; Basu, J.; Das, G. C.; Mukherjee, S.; Mitra, M. K.; Ohji, T.
<x xml:space="preserve">Abstract</x> Nanostructured Aluminum Nitride (AlN) has been prepared by carbothermal reduction followed by nitridation (CTRN) of alumina gel over a temperature range 1200°C–1350°C and time period of 30 min to 3 h. Before heat treatment the gel is repeatedly evacuated and purged with ammonia. The nanopores of the gel are filled with ammonia which acts as a source of in situ nitrogen at heat‐treatment temperature. Dextrose also decomposes at the reduction temperature and generates ultrafine carbon. The stability diagram of the carbon saturated Al–N–O system is constructed and it shows that extremely low partial pressure of oxygen is required for the stability of AlN. The ultrafine carbon as well as hydrogen from the cracking of ammonia is not sufficient to create the extremely low partial pressure of oxygen required for the stabilization of AlN. So the sample is heat treated in charcoal boat in nitrogen atmosphere to achieve an extremely low partial pressure of oxygen required for the formation of AlN. The material has been characterized through XRD, FESEM, and HRTEM analyses. The spherical particle size of AlN is obtained ∼21 nm.